Knowledge Sharing, Organizational Culture, Intellectual Capital, and Organizational Performance - Dwi Irawan; Elvin Bastian; Imam Abu Hanifah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
This study aims to examine the influence of knowledge sharing and organizational culture toward organizational performance with intellectual capital as an intervening variable. The questionnaire was sent to 71 general managers of manufacturing companies, and 60 questionnaires were returned. The data of this research were analyzed using structural equation modelling (SEM) method, with Partial Least Square (PLS) approach. The results of this study indicated that knowledge sharing had a significant positive effect on human capital, yet no significant effect on structural capital and relational capital. Knowledge sharing also had no significant effect on organizational performance. Meanwhile, the organizational culture had a significant positive effect on human capital, structural capital, and relational capital and also significant effect on organizational performance. The influence of knowledge sharing on organizational performance was only partially mediated by intellectual capital or only mediated by human capital, while the influence of organizational culture on organizational performance was not mediated by intellectual capital which consists of human capital, structural capital, and relational capital.